2019
DOI: 10.1007/s10554-019-01536-6
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular basal inflow and outflow tract diameters overestimate right ventricular size in subjects with sigmoid-shaped interventricular septum: a study using three-dimensional echocardiography

Abstract: Purpose: Sigmoid-shaped ventricular septum (SS), a frequently encountered minor abnormality in echocardiographic examinations of the elderly, may have some influence on RV shape. We aimed to determine the influence of SS on the accuracy of the 6 RV linear diameter measurements in the light of three-dimensional echocardiographic (3DE) RV volume. Subjects and Methods: The aorto-septal angle (ASA) was measured in the parasternal long-axis view using two-dimensional echocardiography (2DE) as an index of SS in 70 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Since the elongated aorta cannot be expected to curl as much as the small vessels, the point where it will move when it is extended is the partly free starting point, namely the aortic root, and the aortic root enters into the heart, which narrows the angle between the aorta and the septum (Figure 3). Some publications show that the frequency of sigmoid septum increases with age, 2,6) and observations support this information. However, according to our data, it can be suggested that the septum reverting to the sigmoid shape is due to the elongation of the aorta, and this is more related to the duration of HT than the effect of age.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Since the elongated aorta cannot be expected to curl as much as the small vessels, the point where it will move when it is extended is the partly free starting point, namely the aortic root, and the aortic root enters into the heart, which narrows the angle between the aorta and the septum (Figure 3). Some publications show that the frequency of sigmoid septum increases with age, 2,6) and observations support this information. However, according to our data, it can be suggested that the septum reverting to the sigmoid shape is due to the elongation of the aorta, and this is more related to the duration of HT than the effect of age.…”
Section: Discussionmentioning
confidence: 62%
“…5) Apart from these articles, AoSA has been mentioned in several studies on septal hypertrophy and the subaortic membrane, asymmetric septal hypertrophy, and subaortic stenosis related to the thickness of the septum and restriction of the subaortic flow. [6][7][8][9][10][11] In addition, in a study published in 2012, it was stated that AoSA was associated with the central blood pressure (BP) and that it changed with antihypertensive treatment. 12) In another study conducted in 2014, AoSA was shown to be correlated with diastolic dysfunction.…”
mentioning
confidence: 99%
“…A 2018 ARIC study of 1,004 elderly participants also showed that a lower RVEF and lower RVEF/PASP ratio are linearly associated with an increased risk of incident heart failure or death, suggesting an important and underrecognized role of RV dysfunction in the progression to heart failure. That study also suggested the potential utility of 3DE for accurate assessment of RV performance (21)(22)(23).…”
Section: Discussionmentioning
confidence: 70%